Pendekatan Pendidikan dan Pola Asuh Orang Tua Terhadap Remaja Dalam Menghadapi Krisis Moral Pergaulan Bebas di Era Digital - Hilyatul azkia; Miftahurohmah, Rifda Nur; Nafisah, Afra (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2026)
The phenomenon of promiscuity among teenagers is increasingly worrying along with the rapid development of digital technology. Unlimited access to information and the strong influence of social media have had a significant impact on the mindset and behavior of adolescents, especially in shaping lifestyles that deviate from social and moral norms. This article aims to examine educational approaches and parenting patterns in responding to the moral crisis experienced by adolescents due to involvement in promiscuity. Through descriptive qualitative methods, this article analyzes the impact of unsupervised use of social media, including exposure to negative content and public figures that adversely affect adolescents' values. The results of the analysis show that the role of parents has a significant contribution in shaping adolescents' moral resilience through open communication, providing emotional attention, and internalizing spiritual and ethical values. Parents not only function as caregivers, but also as educators and moral development agents who play an active role in assisting children's psychosocial development. Thus, family empowerment, especially in terms of strengthening the parenting function, is the main strategy in overcoming the negative impact of promiscuity and building a resilient and integrity adolescent character amid the increasingly complex challenges of the digital era.